Between Resistance and Adaptation: Indigenous Peoples and the Colonization of the Chocó, 1510 1753 (2022)
eng: This is a study of the interactions between Indians and Spaniards in the Chocó throughout much of the colonial period, revealing the complexity of inter-ethnic relations in frontier regions. The book considers the changing relationships not only between Spaniards and Indians but also between factions of both groups, showing how Spaniards and Indians sometimes allied with each other against other ethnically mixed groups with different agendas.